2021
DOI: 10.1155/2021/9947704
|View full text |Cite
|
Sign up to set email alerts
|

Improved Mitigation Method for the Multipath Delays of BDS‐3 Code Observations with the Aid of a Sparse Modeling Algorithm

Abstract: Global navigation satellite systems are essential for positioning, navigation, and timing services. The quality and reliability of satellite observations determine the system performance, especially in the case of the newly launched global BDS-3 service. However, analyses of multipath delays in BDS-3 satellite observations suggest that there are appreciable errors at different frequencies. Improvement of the accuracy and precision of positioning, navigation, and timing services provided by BDS-3 requires the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…According to the testes of multi-GNSS and multifrequency observations based on the proposed integrated Doppler and phase method, it is indicated that velocity residuals present the Normal distributions for all phase observations, where the velocity residuals RMS of each system are similar with. Moreover, from the TABLE 4, it is found that the BDS-3 slightly outperforms the GPS, Galileo and Glonass, which is mainly benefited from the lower noise for the new-generation BDS-3 satellites [5,26]. Furthermore, there are not significant differences between BDS-3, GPS and Galileo in determining velocity, while the Glonass satellite signal should be carefully processed.…”
Section: B Results Of the Proposed Velocity Determination Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…According to the testes of multi-GNSS and multifrequency observations based on the proposed integrated Doppler and phase method, it is indicated that velocity residuals present the Normal distributions for all phase observations, where the velocity residuals RMS of each system are similar with. Moreover, from the TABLE 4, it is found that the BDS-3 slightly outperforms the GPS, Galileo and Glonass, which is mainly benefited from the lower noise for the new-generation BDS-3 satellites [5,26]. Furthermore, there are not significant differences between BDS-3, GPS and Galileo in determining velocity, while the Glonass satellite signal should be carefully processed.…”
Section: B Results Of the Proposed Velocity Determination Methodsmentioning
confidence: 97%
“…For example, compared with BDS-2 and other GNSS, the new-generation BDS-3 satellites are equipped with high-stability onboard clock, inter-satellite link and updates the modulation of transmitting signals [2]. Meanwhile, it is indicated that user range errors (URE) of BDS-3 signals are better than 0.5m, and the superior positioning performance can be obtained, which is mainly benefited from the abundant observations provided by BDS-3 [3][4][5]. The civilian signals of BDS-3 satellites reaching up to five frequencies, namely B1C, B1I, B2a, B2b and B3I, are synchronous service.…”
Section: Introductionmentioning
confidence: 99%